2020
DOI: 10.1186/s40068-020-00168-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling scenarios for sustainable water supply and demand in Addis Ababa city, Ethiopia

Abstract: Background: The city of Addis Ababa is under rapid development and there are enormous construction activities along with rapid urbanization, and industrialization. These anthropogenic actions combined with population growth rate are affecting the water demand of the city. The overall purpose of this study is to model water supply and demand of the city and to identify potential water management strategies that supports the sustainable development goal number six (SDG6)-clean water and sanitation. Methods: We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
(8 reference statements)
1
11
0
2
Order By: Relevance
“…12 , which will support the achievement of SDG 6 of clear water and sanitation. Studies also support this study's results that IWMS is better than another scenario (Alemu & Dioha, 2020 ; Kitessa et al, 2021a ). Furthermore, Fig.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…12 , which will support the achievement of SDG 6 of clear water and sanitation. Studies also support this study's results that IWMS is better than another scenario (Alemu & Dioha, 2020 ; Kitessa et al, 2021a ). Furthermore, Fig.…”
Section: Resultssupporting
confidence: 85%
“…Recent studies indicated that IWMS intervention saves more water than individual management approaches (Alemu & Dioha, 2020 ; Kitessa et al, 2021a , 2022 ). DSMS that include structural water-saving and advanced or technical water-saving technology can result in water-saving potentials of 6.97% and 9.82% by 2050, respectively (Kou et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity and frequency of extremes can be easily changed by climate change and the changes in climate extremes and their impacts on a variety of physical and biological systems examined by the Intergovernmental Panel on Climate Change (IPCC) and their effects can also contribute to global warming (IPCC 2007). Many factors such as the expansion of cities, and fast population growth rate along with migration from rural to urban areas pose a major challenge for city planners and also contributes to increasing climate change (WHO and UNICEF 2006;Alemu and Dioha 2020). Using various General Circulation Models, Feyissa et al (2018) suggested future climatic changes and argued that a rise in temperature will exacerbate the urban heat highland effects in warm seasons and an increase in precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Addis Ababa city population is increasing alarmingly due to internal migration and the high population growth rate of the city. The capital city is under rapid development with enormous construction activities along with rapid urbanization and industrialization (Alemu and Dioha 2020). Using various General Circulation Model, Feyissa et al.…”
Section: Introductionmentioning
confidence: 99%